ANALYSIS OF ENTREPRENEURSHIP-BASED BUSINESS OPPORTUNITIES AS A STRATEGY FOR FINANCIAL INDEPENDENCE ISLAMIC EDUCATION - khoiroh, Ummul; Abdullah (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze entrepreneurship-based business opportunities as a strategy for independent Islamic education financing by emphasizing the identification of business opportunities, the integration of Islamic entrepreneurial values, the contribution of business units to education financing, and business development strategies. Using a qualitative approach through case studies and in-depth interviews, this study found that Islamic boarding school business units developed based on internal and external needs are able to make a significant contribution to the sustainability of education financing. These findings indicate that Islamic boarding school entrepreneurship is not only oriented towards economic aspects but is also influenced by Islamic values in institutional governance. This study enriches the study of Islamic education financing by presenting a values-based entrepreneurial perspective. However, this study has limitations in the scope of the case and the methodological approach, so the findings cannot be generalized widely. Therefore, further research with a more diverse scope and method is recommended to strengthen and expand the findings of this study.